Polynomial matrices over a factorial domain and their factorization with given characteristic polynomials - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions for the existence of a unital divisor with given characteristic polynomial of a polynomial matrix over a factorial domain.